A NEW TREE FROG OF THE GENUS KURIXALUS YE, FEI & DUBOIS, 1999 (AMPHIBIA: RHACOPHORIDAE) FROM WEST KALIMANTAN, INDONESIA - Mediyansyah Mediyansyah; Amir Hamidy; Misbahul Munir; Masafumi Matsui (BRIN Publishing (Penerbit BRIN), 2019)
Kurixalus absconditus sp. nov., a new species of tree frog of the genus Kurixalus, described from West Kalimantan on the basis of molecular phylogenetic and morphological evidence. The new species can be distinguished from its congeners by a combination of following morphological characters: having smaller body size, more prominent of mandibular symphysis, skin smooth on throat, vomerine odontophores two oblique series touching anterior corner of choanae and widely separated, vomerine teeth thick, buccal cavity narrow and deep, choanae with teardrop shaped, single vocal slit, weakly crenulated dermal fringe on fore- and hindlimbs.